Silencing of Escherichia coli bgl promoter by flanking sequence elements. - Schnetz, K (1995)
Silencing of a transcriptional unit by flanking sequence elements has so far only been described for eukaryotic systems. Here, a similar system is described in bacteria. The Escherichia coli bgl operon (beta-glucoside utilization) is normally cryptic due to very low promoter activity. However, low activity is not attributable to the quality of the promoter itself but is caused by its chromosomal context. The bgl promoter is perfectly active when tested outside of its normal context of a stretch of a few hundred base pairs. In addition, other promoters become inactivated when placed into the bgl region. Both the deletion of an upstream sequence element and the replacement of sequences located downstream result in promoter de-repression, demonstrating that silencing of promoters within this stretch of DNA in vivo is an active process brought about by the combined action of upstream and downstream chromosomal elements.